1998
DOI: 10.1159/000045050
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy Complicating Diabetic Glomerulosclerosis

Abstract: A retrospective study was done on 66 diabetic patients who had renal biopsies performed during 1979–1994. This review shows 10 patients who presented IgA nephropathy associated with diabetic nephropathy. Six patients had insulin-dependent diabetes mellitus and 4 patients non-insulin-dependent diabetes mellitus. All patients presented with proteinuria and 7 had hematuria. Four patients presented with renal impairment. Histologic evaluation disclosed the presence of thickened glomerular basement membranes and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
4
18
1
Order By: Relevance
“…Moreover, IgA nephropathy was found to be the commonest NDRD in other studies. 20,21 But other studies 15,17 showed that crescentic glomerulonephritis or acute tubulointerstitial nephritis and postinfectious glomerulonephritis were the commonest NDRD. Several observations suggest that common occurrence of IgA nephropathy in diabetic patients is not coincidental.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, IgA nephropathy was found to be the commonest NDRD in other studies. 20,21 But other studies 15,17 showed that crescentic glomerulonephritis or acute tubulointerstitial nephritis and postinfectious glomerulonephritis were the commonest NDRD. Several observations suggest that common occurrence of IgA nephropathy in diabetic patients is not coincidental.…”
Section: Discussionmentioning
confidence: 99%
“…Several observations suggest that common occurrence of IgA nephropathy in diabetic patients is not coincidental. [20][21][22] Diabetic itself by affecting either glomerular structure and functioning and/or nonenzymatic glycation of immunoglobulin may facilitate the development of immunopathological alterations. 23 In support of this notion, superimposed IgA nephropathy on DN was associated with higher IgA levels when compared with DN alone.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of NDRD in diabetic patients is not clear. Some authors have suggested that the predisposition of DN to glomerulonephritis could be attributed to enhanced exposure of antigenic cellular components, triggering immune responses [36].…”
Section: Discussionmentioning
confidence: 99%
“…Primary glomerulonephritis, such as IgA nephropathy, has been reported to be superimposed on a background of diabetic glomerulosclerosis in patients with type 1 and 2 diabetes mellitus [25,26]. This could be a possibility in this reported case, though patient's diabetes mellitus was well-controlled (HbA1c 7%, no proteinuria, normal renal function and no diabetic retinopathy).…”
Section: Discussionmentioning
confidence: 70%